TI_GERICHTE 12.2014.190 vom 14. Dezember 2015 , Contratto di pegno - esistenza del debito garantito - onere di allegazione -errore - dolo - TI Tribunale d'appello (2015)
Contratto di pegno - esistenza del debito garantito - onere di allegazione -errore - dolo